PHENOMENON OF LIFE COMPETENCE OF A PERSONALITY AND ITS PLACE IN THE PROFESSIONAL ACTIVITY OF FUTURE PSYCHOLOGISTS (Psychology Travelogs, 2025)
The article explores the concept of life competence as a fundamental integrative quality of the individual, particularly relevant for students in the field of psychology. The authors define and differentiate between the terms “competence,” “competency,” and “life competence,” highlighting their dynamic nature and close connection with professional effectiveness. Life competence is considered as a multidimensional construct that encompasses cognitive, emotional, social, communicative, and behavioral components, which together enable the individual to adapt to various life challenges, make informed decisions, interact constructively with others, and engage in personal and professional growth. Particular attention is paid to the relevance of life competence in the professional training of psychologists, where the ability to manage one’s inner states, maintain healthy interpersonal relationships, act independently and responsibly, and reflect critically on experience is essential. Theoretical foundations provided by Bandura (self-efficacy), Maslow (self-actualization), Rogers (congruence and self-acceptance), and Erikson (identity development) are reviewed as key frameworks for understanding life competence. The article substantiates the need to integrate life competence development into the educational process through experiential learning, reflexive practices, and psychologically safe environments. It is argued that fostering life competence in future psychologists not only supports their personal well-being and self-realization but also enhances their capacity for empathic and ethical professional work. The findings and conclusions of the article can be useful for educators, curriculum developers, and practitioners in the field of psychological education and professional development.
Keywords: phenomenon; life competence; competence; professional activity; models of life competence